Analisis Strategi Pengembangan Budidaya Ikan Nila pada Usaha Bapak Gandi di Desa Darat Sawah Kecamatan Seginim - Delta Maryeta Putri; Rika Dwi Yulihartika; Herri Fariadi (Jurnal Multidisiplin Dehasen (MUDE), 2026)
Freshwater fish farming is a business that promises quite large profits that can provide greater selling value. This study aims to analyze internal and external factors in the development of Mr. Gandi's tilapia fish farming in Darat Sawah Village, strategies that can be applied in the development for Mr. Gandi's Tilapia Farming in Darat Sawah Village, Seginim Sub-District, South Bengkulu Regency. This research uses a descriptive quantitative research method, and uses data collection techniques with Observation, Interviews, and Documentation using SWOT analysis Strengths (strengths), Weaknesses (Weaknesses), Opportunities (Opportunities), Threats (Threats). The results of the research revealed that the main strength for Mr. Gandi's Tilapia Farming business lies in the availability of land and ponds 4.00 and the experience and skills of farmers 4.00. Meanwhile, the main weakness identified is the limited facilities and infrastructure for cultivation 1.66. The biggest opportunity for this business is the high market demand for tilapia fish and the market price of tilapia fish of 4.00. On the other hand, the main threats are environmental and weather conditions. Strategies that can be implemented are: 1. Developing a sustainable fish pond system according to land conditions. 2. Utilizing a water recirculation system to conserve water and maintain pond water quality. 3. Implementing a regular cleaning schedule to stabilize water flow and quality. 4. Collaborating with suppliers of superior, quality-tested seeds. 5. Establishing your own nursery to control seed stock and reduce long-term costs. 6. Using high-quality feed appropriate to the age of the fish for optimal growth. 7. Implementing a feeding program based on the fish's age stages: seed, grow-out, and harvest. 8. Building marketing partnerships with local buyers or distribution networks.